'Central Wheat HS562' - a high yielding wheat variety for timely sown production conditions of Northern Hill Zone - Pal1, Dharam; Patial1, Madhu; Prabhu2, KV; Kumar1, J; Watpade1, Santosh; Yadav3, RN; Kumar2, Sanjay; Sharma2, RK; Singh2, GP; Yadav2, Rajbir; 2, Vinod; Singh2, Anju M; et al. (Journal of Cereal Research, 2017)
'Central Wheat HS562' - a high yielding wheat variety was released and notified by Central Sub-Committee on Crop Standards, Notification and Release of Variety, Ministry of Agriculture, Govt of India for cultivation under timely sown, rainfed and irrigated production conditions of Northern Hills Zone (NHZ). 'Central wheat HS562' produced an average grain yield of 36 q/ha with 6.2% grain yield advantage over best check HS507 under rainfed conditions of NHZ. Similarly, it recorded an average grain yield of 52.7 q/ha with 8.4% grain yield advantage over the best check HS507 under irrigated conditions of NHZ. This variety has ability to withstand the stripe rust pressure and recorded average coefficient of infection (ACI) ranging 3.6 - 13.0 under artificial inoculation conditions. It possesses good chapatti score (7.54) and bread making quality score (6.22) out of 10 along with good amount of Fe (38.4ppm) and Zn (34.5ppm) contents. Large scale deployment of this variety in North-Western Himalayan Region through various Government and non-Government organizations is anticipated not only to enhance wheat productivity of this region but would also curtail rust inoculum flow from hills to the wheat grown in North Western Plains Zone of India.Â Doi.org/ 10.25174/2249- 4065/2017/76420